Analisis Kesalahan Berbahasa pada Berita tentang Perguruan Tinggi dalam Media Daring Detik.com berdasarkan Kategori Linguistik - Sevti Putri Thavany; Ifah Afivah; Lia Mutiara; Ai Siti Nurjamilah (Jurnal Bintang Pendidikan Indonesia, 2025)
This research was conducted with the aim of analyzing language errors based on linguistic categories in news about higher education published on the online media Detik.com. The approach applied in this research is descriptive qualitative, which focuses on analyzing and describing language errors in DetikEdu Higher Education category news articles published by Detik.com. The research results showed that of the 15 news stories, the fewest language errors occurred in the phonology category with a total of 5 errors and the most language errors were in the use of Enhanced Spelling (EYD) with a total of 33 errors. Meanwhile, other language errors include morphology with a total of 24 errors, syntax with a total of 23 errors, and semantics with a total of 17 errors.